Idiopathic pleuroparenchymal fibroelastosis: three-dimensional computed tomography assessment of upper-lobe lung volume. Issue 6 (22nd December 2022) - Fukada, Atsuki; Suzuki, Yuzo; Mori, Kazutaka; Kono, Masato; Hasegawa, Hirotsugu; Hashimoto, Dai; Yokomura, Koshi; Imokawa, Shiro; Tanaka, Yuko; Inoue, Yusuke; Hozumi, Hironao; Karayama, Masato; et al.
Background: Idiopathic pleuroparenchymal fibroelastosis (iPPFE) is a rare interstitial lung disease characterised by predominant upper-lobe fibrosis involving the pleura and subpleural lung parenchyma. Despite its poor prognosis, there is no consensus on prognostic determinants of iPPFE to date. Because volume loss in the upper lobe is a distinct feature of iPPFE, we hypothesised that the lung volume of the bilateral upper lobes (upper-lobe volume) accurately indicates disease severity and mortality risk in iPPFE patients. Methods: This retrospective study assessed two cohorts of 132 patients with iPPFE (69 in Hamamatsu cohort; 63 in Seirei cohort) and 45 controls. Each lobe volume was quantitatively measured using three-dimensional computed tomography at the time of iPPFE diagnosis and standardised using predicted forced vital capacity. Results: The standardised upper-lobe volume in iPPFE patients was less than half that of controls, whereas the lower-lobe volume did not decrease. iPPFE patients with lower standardised upper-lobe volume had significantly shorter survival rates than those with higher volume (median survival: 6.08 versus 2.48 years, p<0.001). In multivariate analysis, the lower standardised upper-lobe volume was significantly associated with increased mortality adjusting for age, sex and forced vital capacity (HR 0.939). A composite scoring model, including age, sex and standardised upper-lobe volume, better predicted risk of death than the gender-age-physiology model. Conclusion: Assessment of upper-lobe volume provides useful information for managing iPPFE by evaluating disease severity and mortality risk in clinical practice. This novel method for quantitative measurements of upper lung lobe volume using standardised three-dimensional computed tomography is useful for assessing disease severity and mortality risk in patients with idiopathic pleuroparenchymal fibroelastosis https://bit.ly/3bHlOPD